The use of pre-occlusive balloons for reduction of perioperative bleeding in patients with placenta percreta: tertiary centre experience and literature review - Morozovaitė, Lina; Šiaudinytė, Ieva; Volochovič, Jelena; Dementavičienė, Jūratė (Lietuvos chirurgija, 2017)
Background / Objective Abnormal penetration of chorionic villi into the wall of uterus is called invasive placenta. The most dangerous type is placenta percreta. It can lead to massive bleeding, which is one of the most serious complications. In order to reduce blood loss during operation intraoperative balloon occlusion of uterus supplying vessels could be use. Our aim is to present the management of perioperative balloon occlusion for two patients with antenatal diagnosis of placenta percreta, compare the prophylaxis of bleeding and review literature. Patients and Methods We carried out a retrospective analysis of medical history of two patients, compared interventional radiology methods between these cases and performed a literature review. Results Two patients with antenatal diagnosis of placenta percreta were determined to undergo an elective cesarean section. Preoperative balloon insertion and inflation after birth was used for massive bleeding prophylaxis. In first case balloons were deflated only after transferring the patient to the Intensive care unit. Four hours after operation internal bleeding was suspected and laparotomy was performed. Stumps of vessels were revised. In addition to this, left internal iliac artery was ligated. In the second case balloons were deflated and drawn out before the end of the cesarean section. Hemostasis was checked again. Conclusions Placenta percreta is a threatening pathology in obstetrics and can cause massive bleeding. The treatment of patients should be scheduled in advance. Interventional radiology methods help to reduce blood loss significantly. On purpose to ensure hemostasis, pre-occlusive balloons should be deflated before the end of operation.